2020
DOI: 10.31557/apjcc.2020.5.s1.43-50
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patient Satisfaction and Perception of Chemotherapy Services During COVID-19 Pandemic in Central Java, Indonesia

Abstract: Background: The COVID-19 pandemic affects all healthcare services, including cancer care. Consequently, our institution implemented several changes in accordance with the National guidelines for managing COVID-19 transmission. However, the patients’ perception of such changes is unknown. The objective of this study is to explore the knowledge of cancer patients on COVID-19, their perceptions towards the changes in oncology service, and to identify key elements that contribute to their level of anxiety or comfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The vast majority of the respondents (96.2%) stated that during their hospitalization, doctors and nurses were equipped with appropriate personal protective equipment, and the rules of the sanitary regime were respected, in particular keeping a 2 m distance (76.40%) in the waiting room and registration room. Similarly, in the studies by Prajoko and Supit [ 24 ], the vast majority of patients believed that the hospital’s safety policy during the COVID-19 pandemic was appropriate. Therefore, it can be assumed that the application of procedures increases the sense of patient safety and reduces the level of anxiety and stress, although these activities do not provide a 100% guarantee in the prevention of coronavirus transmission.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The vast majority of the respondents (96.2%) stated that during their hospitalization, doctors and nurses were equipped with appropriate personal protective equipment, and the rules of the sanitary regime were respected, in particular keeping a 2 m distance (76.40%) in the waiting room and registration room. Similarly, in the studies by Prajoko and Supit [ 24 ], the vast majority of patients believed that the hospital’s safety policy during the COVID-19 pandemic was appropriate. Therefore, it can be assumed that the application of procedures increases the sense of patient safety and reduces the level of anxiety and stress, although these activities do not provide a 100% guarantee in the prevention of coronavirus transmission.…”
Section: Discussionmentioning
confidence: 87%
“…In the studies conducted by Prajoko and Supit [ 24 ], as many as 81% of patients receiving chemotherapy were afraid of the SARS-CoV-2 virus infection during their hospitalization, and 13.6% of the respondents considered discontinuing the treatment. Similarly, studies conducted by Joode et al [ 25 ] showed that cancer patients were concerned about the consequences of the pandemic and its influence on the treatment process.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Patients were categorized into four main groups depending on history of COVID-19 contact, clinical symptoms, and laboratory results to be managed accordingly. 13 Admitted patients are obligated to wear facemask and maintain at least 1 m distance with other people at all time. Only one patient companion are allowed to enter the treatment facility and the patient needs to go into the consultation room alone.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it has become the preferred treatment for hematological tumor diseases (7)(8)(9). However, in recent years, some scholars have pointed out that chemotherapy can cause irreversible damage to the function and structure of the female ovary, leading to amenorrhea and infertility, etc., causing certain psychological pressure to patients (10,11). Studies have shown that chemotherapy-induced amenorrhea and sexual dysfunction are closely related to the secretion of sex hormones (12).…”
Section: Introductionmentioning
confidence: 99%